Gambaran Respon Time Pasien Pada Masa Pandemi COVID-19 Di Instalasi Gawat Darurat (IGD) RSUD Arifin Achmad Provinsi Riau - Erwin; Mahdalena Mahyudin; Hellena Deli (HEALTH CARE : JURNAL KESEHATAN, 2021)
Indonesia is currently being hit by the Covid-19 pandemic outbreak, so it affects patients who come to the emergency room for treatment, especially in the patient's response time. During the Covid-19 pandemic, the patient's response time is getting longer, this is because during the pandemic there are many triage steps that must be taken. Patients who come for treatment at the ER must be screened for Covid-19 first. Purpose this study is to know the description of patient response time during the Covid-19 pandemic. This study uses a quantitative descriptive method. This research was conducted in February 2021. The sample in this study were 87 people who were selected by accidental sampling technique. The results showed that the majority of respondents aged 31-50 years were 34.5%, male gender was 57.5%, medical diagnosis was 79.3%, no referral patient was 88.5%, the level of emergency was with ATS. 3 and ATS 4 as much as 44.8%. The majority of patients' response time got a response time that was according to the standard as much as 90.8%. Patient response time has not been carried out fully according to standards. It is hoped that the emergency room nurses can increase the response time to patients in order to prevent death or permanent disability from a disease.